2014
DOI: 10.1111/acps.12257
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar or borderline: a clinical overview

Abstract: This review of the literature indicates that these two conditions, bipolar illness and borderline personality, are different and can be distinguished. The much stronger biological and genetic evidence for bipolar illness in particular suggests that the two conditions can be reasonably seen as different kinds of clinical entities, namely a biological disease versus a psychosocially caused clinical picture. If this interpretation is correct, similarities between the two conditions, such as mood lability and impu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 86 publications
3
49
0
1
Order By: Relevance
“…By contrast, several reviews have concluded that the empirical evidence does not support a link between BPD and the BD spectrum (Dolan-Sewell et al, 2001;Paris, 2004). A recent clinical overview (Ghaemi et al, 2014) pointed out that the two disorders are distinguishable clinically and diagnostically, and hypothesized that BD can be seen as a genetically based biological disease, whereas BPD should be considered a psychosocially caused disorder. However, as in the case of other major mental disorders, hereditary, biological and environmental factors may influence the pathogenesis and the clinical expression of bipolar spectrum disorders in various ways, so contributing to the extreme heterogeneity of clinical presentations.…”
Section: Psychological Faults Behavioral Consequencesmentioning
confidence: 99%
“…By contrast, several reviews have concluded that the empirical evidence does not support a link between BPD and the BD spectrum (Dolan-Sewell et al, 2001;Paris, 2004). A recent clinical overview (Ghaemi et al, 2014) pointed out that the two disorders are distinguishable clinically and diagnostically, and hypothesized that BD can be seen as a genetically based biological disease, whereas BPD should be considered a psychosocially caused disorder. However, as in the case of other major mental disorders, hereditary, biological and environmental factors may influence the pathogenesis and the clinical expression of bipolar spectrum disorders in various ways, so contributing to the extreme heterogeneity of clinical presentations.…”
Section: Psychological Faults Behavioral Consequencesmentioning
confidence: 99%
“…Several reviews have concluded that empirical evidence did not support a link between BPD and the BD spectrum (5,6). A recent clinical overview (7) concluded that the two disorders are distinguishable clinically and diagnostically and hypothesized that BD should be seen as a genetically based biological disease, whereas BPD should be considered as a psychosocially caused disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Gunderson and Phillips (33) point out that depressive disorder in BPD shows a qualitatively different characteristic than in major depression, being more developmentally and interpersonally based. Mood swings in BD should be more spontaneous and less responsive to environmental triggers than in BPD (7). This perspective is essentially based on the assumption that reactive, unstable, depressive, irritable, anxious and labile mood, with superimposed paroxysms of rage, described by BPD criteria, should be relegated into the personality realm, whereas only classical non-reactive episodic depressive changes are 'true' mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between bipolar disorder and borderline personality disorder (BPD) has been the subject of intense interest, with at least a dozen review articles examining and discussing their interface (Antoniadis, Samakouri, & Livaditis, 2012;Barroilhet, Vohringer, & Ghaemi, 2013;Bayes, Parker, & Fletcher, 2014;Belli, Ural, & Akbudak, 2012;Coulston, Tanious, Mulder, Porter, & Malhi, 2012;Dolan-Sewell, Krueger, & Shea, 2001;Elisei, Anastasi, & Verdolini, 2012;Fiedorowicz & Black, 2010;Ghaemi, Dalley, Catania, & Barroilhet, 2014;Paris, 2004;Smith, Muir, & Blackwood, 2004;Sripada & Silk, 2007). Several years ago, it was suggested that BPD had "come of age" (Oldham, 2009); however, the thesis of the present article is that BPD remains a second-class diagnostic citizen and has been subjugated to this lesser role by efforts to promote bipolar disorder.…”
Section: Mark Zimmerman MDmentioning
confidence: 99%